Implementasi Sistem Keamanan Jaringan Menggunakan Outline VPN Berbasis VPS Server di RSUD xyz - achmad, dany; Muhammad Faishol Amrulloh (Indexia, 2026)
Network security is a crucial aspect in managing information systems in hospitals, especially in protecting patient data and medical records, XYZ Regional General Hospital currently has not implemented a Virtual Private Network (VPN) to secure its internal network connections. This study aims to implement a network security system using a VPS Server-based Outline VPN as a solution to improve data protection and hospital network access. With a case study method specifically to solve this problem, Implementation is carried out by designing and configuring Outline VPN on a VPS, as well as testing its effectiveness in encrypting and securing network connections. The expected results are that the use of a VPS Server-based Outline VPN can improve hospital network security by encrypting data traffic and preventing unauthorized access. This system provides signals in network access management without dependence on third-party VPN service providers.